Effect of Thermal Pretreatments on Phosphorylation of Corypha umbraculifera L. Stem Pith Starch: A Comparative Study Using Dry-Heat, Heat-Moisture and Autoclave Treatments - Basheer Aaliya (MDPI AG, 2021)
Talipot starch, a non-conventional starch source with a high yield (76%) from the stem pith of talipot palm (Corypha umbraculifera L.) was subjected to three different thermal treatments (dry-heat, heat-moisture and autoclave treatments) prior to phosphorylation. Upon dual modification of starch with thermal treatments and phosphorylation, the phosphorous content and degree of crosslinking significantly increased (p ≤ 0.05) and was confirmed by the increased peak intensity of P=O and P–O–C stretching vibrations compared to phosphorylated talipot starch in the FT-IR spectrum. The highest degree of crosslinking (0.00418) was observed in the autoclave pretreated phosphorylated talipot starch sample. Thermal pretreatment remarkably changed the granule morphology by creating fissures and grooves. The amylose content and relative crystallinity of all phosphorylated talipot starches significantly decreased (p ≤ 0.05) due to crosslinking by the formation of phosphodiester bonds, reducing the swelling power of dual-modified starches. Among all modified starches, dry-heat pretreated phosphorylated starch gel showed an improved light transmittance value of 28.4%, indicating reduced retrogradation tendency. Pasting and rheological properties represented that the thermal pretreated phosphorylated starch formed stronger gels that improved thermal and shear resistance. Autoclave treatment before phosphorylation of talipot starch showed the highest resistant starch content of 48.08%.